Present values : essays on economics and aspects of Indian society - Subramanian, S. (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This volume is about economists, economics, and issues of concern to Indian society. Some essays are expository, and some satirical. Together, they offer a commentary on the state of the discipline of economics today, and also on aspects of contemporary India's society and polity. The volume affords insights into, among other things, - the pervasive influence of economists such as Kenneth Arrow and Anthony Atkinson, and thinkers such as Tom Paine, Jonathan Swift, and Dadabhai Naoroji; - the place of markets and game theory (and even crime fiction!) in present-day economics; - the affectations and convoluted mathematization of a good deal of 'mainstream' economics; and - India's recent political climate, and the conduct of various arms of the legislature, the executive, and the judiciary in the country. Engaging and lucidly written, this volume should be of interest to scholars of economics, political science, development studies, South Asian studies, and above all, the general reader"--
OCLC-licensed vendor bibliographic record.
Keywords: Economics -- India; India -- Economic conditions -- 1991-; POLITICAL SCIENCE / Public Policy / Economic Policy; BUSINESS & ECONOMICS / Economics / General